PENGARUH RELAKSASI OTOT PROGRESIF DAN TERAPI KOGNITIF TERHADAP TINGKAT KECEMASAN TAHANAN DI RUANG TAHANAN POLRES KEDIRI - Ariani Sulistyorini* Ahsan** Eko Arik Susmiatin*** (Universitas Muhammadiyah Jember, 2016)
Anxiety is an individual experience which has subjective characteristic, it isoften manisfasted as a disfungtional that mean as difficulty and grief to the eventswhich is not known certainly. The condition often happened on someone’s problem,it is also prisoners. Anxiety has affect an the physic and psycologic. One oftreatment to the anxiety is giving a progressive relaxation muscle and cognitivetherapy. The purpose of this study was to analyze the effect of giving the progressivemuscle relaxation and cognitive therapy to the level of prisoner anxiety. Theresearch design used quasy experiment with pre-post test with control group.Sampling technique of purposive sampling with eighteen respondents that devidedinto two group, those were intervention group and control group. The dataagregation use HARS ( hamilton anxiety rating scale). Based on analyze of mannwhiytney p value 0,034 which is p value ≤ 0,05, so it mean there is on influence ofprogressive muscle relaxation and cognitive therapy to the degree of prisoneranxiety. Based on the result of the study, so the progressive muscle relaxation andcognitive therapy is needed to applied as one of way to prevent of anxietypsycosocial problem to prisoner.